Cancer Therapy with Nanoparticle-Medicated Intracellular Expression of Peptide CRM1-Inhibitor - Sui M; Xiong M; Li Y; Zhou Q; Shen X; Jia D; Gou M; Sun Q (International Journal of Nanomedicine, 2021)
Min Sui,1,* Meimei Xiong,2,* Yuling Li,1,* Qiao Zhou,1 Xiaofei Shen,3 Da Jia,3 Maling Gou,2 Qingxiang Sun1 1Department of Pathology and State Key Laboratory of Biotherapy, West China Hospital, Sichuan University, and Collaborative Innovation Centre for Biotherapy, Chengdu, 610041, People’s Republic of China; 2State Key Laboratory of Biotherapy and Cancer Center, West China Hospital, Sichuan University, and Collaborative Innovation Center for Biotherapy, Chengdu, 610041, People’s Republic of China; 3Key Laboratory of Birth Defects and Related Diseases of Women and Children, Department of Pediatrics, Division of Neurology, West China Second University Hospital, Sichuan University, Chengdu, 610041, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qingxiang Sun; Maling Gou Email sunqingxiang@hotmail.com; goumaling@scu.edu.cnIntroduction: Peptides can be rationally designed as non-covalent inhibitors for molecularly targeted therapy. However, it remains challenging to efficiently deliver the peptides into the targeted cells, which often severely affects their therapeutic efficiency.Methods: Herein, we created a novel non-covalent peptide inhibitor against nuclear export factor CRM1 by a structure-guided drug design method and targetedly delivered the peptide into cancer cells by a nanoparticle-mediated gene expression system for use as a cancer therapy.Results: The nuclear export signal (NES)-optimized CRM1 peptide inhibitor colocalized with CRM1 to the nuclear envelope and inhibited nuclear export in cancer cell lines in vitro. The crystal structures of the inhibitors complexed with CRM1 were solved. In contrast to the covalent inhibitors, the peptides were similarly effective against cells harboring the CRM1 C528S mutation. Moreover, a plasmid encoding the peptides was delivered by a iRGD-modified nanoparticle to efficiently target and transfect the cancer cells in vivo after intravenous administration. The peptides could be selectively expressed in the tumor, resulting in the efficient inhibition of subcutaneous melanoma xenografts without obvious systemic toxicity.Discussion: This work provides an effective strategy to design peptide-based molecularly targeted therapeutics, which could lead to the development of future targeted therapy.Keywords: CRM1, non-covalent inhibitor, crystal structures, DNA nanocomplex, protein engineering